Recording Out-of-Hospital Cardiac Arrest Treatment via a Mobile Smartphone Application: A Feasibility Simulation Study. (4th March 2019) - Sondheim, Samuel E.; Devlin, Joseph; Seward, William H.; Bernard, Aaron W.; Feinn, Richard S.; Cone, David C.
Abstract: Background: Given the demanding nature of out-of-hospital cardiac arrest (OHCA) resuscitations, recordings of the times of interventions in EMS patient care reports (PCRs) are often inaccurate. The American Heart Association developed Full Code Pro (FCP), a smartphone application designed to assist EMS personnel in recording the timing of interventions performed. Through OHCA simulations, this study assessed the group size necessary to use the FCP recording functions accurately and safely without compromising patient care. Program evaluation was based on participant feedback surveys, data accuracy, delays between recording and performing interventions, and delays in care attributed to using the application, stratified by group size. Methods: Simulations of a standard OHCA scenario using the Gaumard TraumaHal mannequin and a dedicated iPhone 5 preloaded with FCP version 3.4 were run with group sizes of 2–6 participants, with group sizes determined by participant availability. Participants included Connecticut certified paramedics and paramedic students who had completed the appropriate coursework. A 7-item feedback survey using a Likert scale established participant feedback on the application. Videos of the simulations were analyzed to assess for delays. One-way analysis of variance with trend analysis was used to test whether outcomes differed by group size and whether differences tended in one direction in parallel with group size. Results: There were 37 simulations, including 142 participants. The feedback survey questions achieved a Cronbach's alpha of 0.91, signifying high reliability, and demonstrated a linear trend supporting greater satisfaction with FCP as group size increases ( p < 0.001). Similarly, increasing group size displayed linear trends with greater numbers of interventions recorded ( p = 0.009) and fewer missed and false recordings ( p = 0.002). Delays revealed significant linear trends ( p = 0.018 for delays in recording and p < 0.001 for delays in care), as increasing group size corresponded with lesser delays. Greatest improvement was noted to be between groups of 3 and 4 participants. Conclusions: OHCA simulations using FCP demonstrate increased provider comfort, increased recording accuracy, and decreased delays as the group size increased. While the application may improve recordings for PCRs and future research, the data suggest a sufficient number of EMS personnel (>3) should be present to achieve reliable data without compromising patient care.